Sistema de diagnóstico de faltas integrado ao sistema de supervisão e controle - Medeiros, Eudes Barbosa de (2008)
Nowadays, the standards given by the “Agência Nacional de Energia Elétrica” the Brazilian regulator agency, requires a high reliable operation of the electric power systems and, as a result, the system operators in the control and operation centers becomes very stressful when the system experiences electric faults since they ought take correct decision to restore the supply in a short time. In addition to that, an avalanche of information, delivered from the Supervisory Control and Data Acquisition (SCADA) reaches the centre of control and the operators need to identify and to interpret these information to take prompt and correct decisions. These conditions increases very much the chance of mistakes by the operators due to the limitation of the human capacity in dealing at the same time with both great volume of information and emotional pressure under stringent situations. For these reasons the professionals of engineering definitely need computational tools capable of effectively analyze the information from the SCADA to support the operator decisions. This work proposes a Fault Diagnosis System (FDS), based on Colored Petri Nets (CPN), which is able to quick identify the system component in fault. The FDS is centralized in the Centre of Control and as such it has the advantage to analyze and to interpret voluminous raw data and generate succinct and directive information to aid the system restoration for faults on both the system network and substations. The proposed method has been tested using part of the distribution network of the distribution utility Companhia Energética do Ceará – COELCE, which includes six stations 69/13kV interconnected by 69kV sub-transmission lines. Several test-cases were applied to the FDS to validate its performance and the delivered reports have been found accurate and effective.